2020
DOI: 10.1021/acs.jnatprod.9b00570
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Salicaceae Acetyl Salicins Using Selective Deacetylation and Acetyl Group Migration

Abstract: In the present work, the synthesis of acetylated salicins, which occur naturally in many Salicaceae species, is reported. The preparation of 2-O-acetylsalicin, 2-O-acetylchlorosalicin, and 2-O-acetylethylsalicin from peracetylated bromosalicin with selective acid-catalyzed deacetylation and one-pot nucleophilic substitution of bromine as the key steps is described. The base-catalyzed O-2 → O-6 acetyl migration afforded 6-O-acetylsalicin derivatives in good yields. Thus, the first synthesis of 6-O-acetylsalicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Recently, 6-O-acetylation by migration of acetyl group from O-2 has been developed. 39 Enzymatic acetylation [40][41][42] has also been applied for the selective introduction of acetyl groups at primary hydroxy groups of sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 6-O-acetylation by migration of acetyl group from O-2 has been developed. 39 Enzymatic acetylation [40][41][42] has also been applied for the selective introduction of acetyl groups at primary hydroxy groups of sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is evidence that acyl-substituents in glucosyl moieties tend to migrate to position 6', where the most stable derivative is formed. (Pearl and Darling 1963;Romanova et al 2020) We therefore deduced 6'-O-benzoylsalicortinol to be an early rearranged intermediate of the tremulacin metabolism and hypothesize that its benzoylation hinders degradation by the enzymes that otherwise quickly break down salicortin. It has often been shown that β-keto acids decarboxylate during metabolic transformation, (Pollack 1978), but in the present case, the ketone of 6-HCH is reduced to an alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…3-Ra was determined as a 2-(hydroxymethyl) phenyl-β-D-glucopyranoside by scrutiny of the 1 H and 13 C NMR, MS, and ECD data. 39 3-Rb was determined as methyl (1S,6S)-1,6-dihydroxy-cyclohex-2-encarboxylate by analysis of its 1D NMR and MS data and TDDFT-ECD calculations at the B3LYP/6-31G*// ωb97xd/def2-TZVP level of theory in methanol with the IEFPCM solvent model (Figure 3). 47 The structure of compound 3 was thereby elucidated unambiguously as shown.…”
Section: Characterization Of Compounds Salixteroside a (1mentioning
confidence: 99%
“…13 C NMR data are given in Figures S81 and S82; (+)ESIMS m/z 309.1 [M + Na] + ; the spectroscopic data are in agreement with the published data. 39 3-Rb was isolated as colorless oil; UV (MeOH) λ max (log ε) 195 (3.74) nm; ECD (MeOH) λ (Δε) 214 (−1.5) nm; 1 H and 13 C NMR data are given in Figures S85 and S86; (+)EIMS m/z 172 [M] + . The absolute configuration of 3-Rb were assigned by TDDFT-ECD analysis (Figure 3).…”
Section: Characterization Of Compounds Salixteroside a (1mentioning
confidence: 99%